Theranostics in breast cancer - Vorster, M.; Hadebe, B. P.; Sathekge, M. M. (Frontiers in Nuclear Medicine, 2023)
Introduction Breast cancer is a complex disease and constitutes the leading cause of cancer in women globally. Conventional treatment modalities include surgery, chemotherapy, radiation therapy, and hormonal therapy; all of these have their limitations and often result in significant side effects or toxicity. Targeted radionuclide therapy based on a theranostic approach has been successfully applied in several malignancies, such as prostate cancer, thyroid cancer, and neuro-endocrine tumours. Several studies have also highlighted the potential of theranostic applications in breast cancer. Aim This review aims to provide an overview of the most promising current and future theranostic approaches in breast cancer. Discussion The discussion includes pre-clinical as well as clinical data on some of the most successful targets used to date. Examples of potential theranostic approaches include those targeting the Human epidermal growth factor receptor 2 (HER2) expression, angiogenesis, aspects of the tumour microenvironment, Gastrin-releasing peptide receptor (GRPR), Prostate-specific membrane antigen (PSMA) and Chemokine receptor 4 (CXCR-4) expression. Several challenges to widespread clinical implementation remain, which include regulatory approval, access to the various radiopharmaceuticals and imaging technology, cost-effectiveness, and the absence of robust clinical data. Conclusion Theranostic approaches have the potential to greatly improve diagnosis, treatment, and outcomes for patients with breast cancer. More research is needed to fully explore the potential of such approaches and to identify the best potential targets, considering feasibility, costs, efficacy, side effects and outcomes.